Advancing Educational Practices: Implementation of Montage Techniques in Early Childhood Learning - Rahman, Ikhwan; Ramadhani, Sri Sauci; Rahmanda, Fanisya; ineng; alfajri (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2024)
Early childhood is a child who is in the process of development, both physical, intellectual, social, emotional and language development that takes place gradually. Therefore, in learning for early childhood, teachers must be able to apply learning methods, one of the learning methods that can be applied is by using the montage technique. This study aims to determine: 1. Planning the Application of Montage Techniques by Teachers to Children Aged 4-5 Years 2. Implementation of the Application of Montage Techniques by Teachers to Children Aged 4-5 Years 3. Factors Influencing the Application of Montage Techniques. This type of research is qualitative research with a descriptive approach. The primary data sources of this study are the principal and teachers while the secondary data sources are documents and books. Data were collected using techniques, observation, interviews, and documentation and processed by reducing, presenting and drawing conclusions. The results of the research conducted were found as follows: (1) Planning the implementation of montage techniques Teachers prepare teaching materials by analyzing the module first, teachers make learning plans (RPPH), (2) Teachers prepare tools and materials for children then teachers explain the steps in montage activities using demonstration methods, (3) Supporting factors include adequate tools and materials, teachers utilize facilities at school then the motivation and enthusiasm given by teachers to children become supporting factors in the implementation of montage techniques. While the inhibiting factors are limited time and the condition of children who are still aggressive and do not follow the rules in activities because of their early age.